Identificação e quantificação das proteínas miofibrilares, isoformas da cadeia pesada de miosina (MyHC) e o amaciamento da carne de bovinos Nelore (Bos indicus) - Malheiros, Jessica Moraes [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
This study aimed to further study the quality of beef in Nellore cattle (Bos indicus). Were used 718 animals finished in feedlot for 90 to 100 days aged 20 to 24 months of herds of four farms that are part of the breeding programs of the grupo Conexão Delta G, PAINT and Nelore Qualitas. The slaughter of animals occurred in commercial refrigerators employees, carcasses were identified and cooled for a period of 24 to 48 hours. After cooling and full establishment of rigor mortis samples of Longissimus dorsi bone (approximate thickness of 2.54 cm) between the 9th and 13th ribs, the left half carcass of each animal were harvested. Samples collected between the 12th and 13th ribs were used to evaluate the physical quality, as the rib eye area (REA), fat thickness (SFT), an index of marbling (IM), cooking loss, staining instrumental meat and shear force (SF). From the rest of the meat, aliquots for analyzes of myofibrillar fragmentation index (MFI) and total lipids (TL) were collected. After the realization of physicochemical analyzes the separation of the data was performed using a selection model of two experimental groups: (1) Group of tender meat (n = 15) and (2) Group of tough meat (n = 15) so as to obtain two contrasting groups for softness by FC. After separation of the groups (30) the identification and quantification of isoforms of myosin heavy chain (MyHC), troponin and desmin was performed by electrophoresis (SDS -PAGE) gels and photo documentation. The average value found for the REA was 72.8 cm2, as expected for Bos indicus, which showed SF and average MFI of 5.73 kg and 32.03 showing correlation of high magnitude and significant between the two parameters (rp = -0.55; p<0.01). With respect to the Index Optical Density (IOD) measured for troponin and desmin was not found different contrasting results for both groups, contrary to what was observed for MyHC, particularly for isoform ...

O presente trabalho objetivou aprofundar os estudos sobre a qualidade da carne bovina em animais Nelore (Bos indicus). Foram utilizados 718 animais terminados em confinamento por 90 a 100 dias com idade entre 20 a 24 meses provenientes de rebanhos de quatro fazendas que integram os programas de melhoramento genético do grupo Conexão Delta G, PAINT e Nelore Qualitas. O abate dos animais ocorreu em frigoríficos comerciais colaboradores, as carcaças foram identificadas e resfriadas por um período de 24 a 48 horas. Após o resfriamento e estabelecimento pleno do rigor mortis foram colhidas amostras do músculo Longissimus dorsi com osso (espessura aproximada de 2,54 cm) entre a 9ª e 13ª costelas, da meia-carcaça esquerda de cada animal. As amostras coletadas entre a 12ª e 13ª costelas foram utilizadas para realização das análises físicas de qualidade, como a área de olho de lombo (AOL), espessura de gordura subcutânea (EGS), índice de marmorização (IM), perdas por cozimento, coloração instrumental da carne e força de cisalhamento (FC). A partir do restante da carne, foram coletadas alíquotas para a realização das análises de índice de fragmentação miofibrilar (MFI) e lipídeos totais (LT). Após a realização das análises físico-químicas foi realizada a separação dos dados através de um modelo de seleção de dois grupos experimentais: (1) Grupo de carne macia (n=15) e (2) Grupo de carne dura (n=15), de forma a obter-se dois grupos contrastantes quanto à maciez através da FC. Após a separação dos grupos (n = 30) foi realizada a identificação e quantificação das isoformas de cadeia pesada de miosina (MyHC), troponina e desmina utilizando a eletroforese (SDS-PAGE) e fotodocumentação dos géis. O Valor médio encontrado para a AOL foi 72,8 cm2, como esperado para animais Bos indicus, os quais apresentaram FC e MFI médio de 5,7 kg e 32,0 demonstrando ...
Keywords: Bovino de corte; Nelore (Zebu); Carne bovina; Carne - Qualidade; Cisalhamento; Confinamento (Animais); Beef